Prarancangan Pabrik Dimetil Eter Dari TKS Dengan Proses Indirect Synthesis Dengan Disain Alat Utama Destilasi Metanol - Muthia Anugerah Fitri; Panca Setia Utama (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The use of LPG as a gas fuel is still needed by the community in various sectors, where in the future the needs of the community will increase as the industry progresses. One of the alternative fuels that can be developed as LPG substitution is Dimethyl Ether. Dimethyl Ether is produced through the process of synthesis and dehydration of methanol from natural gas. Natural gas is a natural resource that can not be renewed, so there are alternative raw materials that are renewable, one of which is empty palm bunches. The plant is planned to operate for 330 days per year and work continuously for 24 hours / day with a capacity of 50,000 tons / year to be established in Dumai, Riau. The main equipment design at the plant is methanol distillation operated at a pressure of 1 atm and feed temperature of 72,580C. Economic analysis of the plant's design shows that the ether dimethyl of empty palm bunches is feasible to be established with the profit the factory gets after tax is Rp. 90.354.036.131/year and payback period of 2,29 years Keywords : Dimethyl Ether, Economic Analysis, LPG, Natural Gas, Plant Design